Ghrelin in the human myometrium - Morrison John J; Earley Padraig; O'Brien Margaret; Smith Terry J (BMC, 2010)
Abstract Background Ghrelin is a 28-amino acid octanolyated peptide, synthesised primarily in the stomach. It stimulates growth hormone release, food intake and exhibits many other diverse effects. Our group have previously determined that ghrelin inhibited human contractility in vitro. The aim of this study therefore, was to investigate the expression of ghrelin, its receptor, the growth hormone secretagogue receptor type 1 (GHS-R1), ghrelin O-acyltransferase (GOAT) which catalyses ghrelin octanoylation, prohormone convertase 1/3 (PC1/3) responsible for pro-ghrelin processing, in human myometrium, during pregnancy prior to labour, during labour and in the non-pregnant state. Modulation of ghrelin and ghrelin receptor expression in cultured myometrial cells was also investigated. Methods mRNA and protein were isolated from human myometrium and the myometrial smooth muscle cell line hTERT-HM; and real-time fluorescence RT-PCR, western blotting and fluorescence microscopy performed. The effects of β-Estradiol and bacterial lipopolysaccharide (LPS) on hTERT-HM gene expression were evaluated by western blotting. Results We have reported for the first time the expression and processing of ghrelin, GHS-R1, GOAT and PC1/3 expression in human myometrium, and also the down-regulation of ghrelin mRNA and protein expression during labour. Furthermore, GHS-R1 protein expression significantly decreased at labour. Myometrial GOAT expression significantly increased during term non-labouring pregnancy in comparison to both non-pregnant and labouring myometrium. Mature PC1/3 protein expression was significantly decreased at term pregnancy and labour in comparison to non-pregnant myometrium. Ghrelin, GHS-R1, GOAT and PC1/3 mRNA and protein expression was also detected in the hTERT-HM cells. Ghrelin protein expression decreased upon LPS treatment in these cells while β-Estradiol treatment increased GHS-R1 expression. Conclusions Ghrelin processing occurred in the human myometrium at term pregnancy and in the non-pregnant state. GOAT expression which increased during term non-labouring pregnancy demonstrating a similar expression pattern to prepro-ghrelin and GHS-R1, decreased at labour, signifying possible myometrial ghrelin acylation. Moreover, the presence of PC1/3 may contribute to pro-ghrelin processing. These results along with the previous in vitro data suggest that myometrially-produced and processed ghrelin plays a significant autocrine or paracrine role in the maintenance of relaxation in this tissue during pregnancy. Furthermore, the significant uterine modulators LPS and β-Estradiol are involved in the regulation of ghrelin and ghrelin receptor expression respectively, in the human myometrium.